PERAN PEMBELAJARAN STATISTIK DALAM PENGEMBANGAN LITERASI NUMERASI SISWA SEKOLAH DASAR - Nasution, Jefri Habibiy; Siregar, Hanif Luthfi (Jurnal Merah Putih Sekolah Dasar, 2024)
The lack of early understanding of basic statistical concepts contributes to low numeracy literacy among Elementary School (SD) students, despite this skill being essential for daily life decision-making. This research aims to analyze and describe the significant role of integrated statistics learning in the elementary curriculum in enhancing students' numeracy literacy, particularly in their ability to interpret data, identify trends, and draw evidence-based conclusions. The study employed a quasi-experimental method with a pre-test and post-test design on an intervention group (receiving project-based statistics learning) and a control group (conventional mathematics learning) involving 80 Grade V students. The research findings demonstrated a significantly higher and statistically significant increase in numeracy literacy scores in the intervention group (p<0.01). Descriptively, the intervention group showed an average increase (Gain Score) of 82.32% (High category), which contrasts sharply with the control group's average increase of only 31.78% (Low category). These findings indicate that structured and contextual statistics learning plays a crucial and effective role as a tool for developing elementary students' numeracy literacy competence, strengthening their quantitative reasoning skills, and laying a solid foundation for data-based thinking.